A three-component, Zn(OTf)2-mediated entry into trisubstituted 2-aminoimidazoles - Lukin, Alexei; Bakholdina, Anna; Kryukova, Anna; Sapegin, Alexander; Krasavin, Mikhail (Beilstein Journal of Organic Chemistry, 2019)
A three-component reaction involving in situ generation of propargylureas and subsequent Zn(OTf)2-mediated cyclocondensation with a primary amine yielded trisubstituted 2-aminoimidazoles. These findings are in contrast to the previously reported base-promoted unimolecular cyclization of propargylureas (leading to 2-imidazolones) and extend the range of Lewis acid-catalyzed azole syntheses based on N-carbonyl propargylamines.
Keywords: alkyne hydroamination; cyclocondensation; Lewis acid catalysis; multicomponent reactions; propargylurea

(untitled) - Pews-Davtyan, A.; Tillack, A.; Schmöle, A.-C.; Ortinau, S.; Frech, M. J.; Rolfs, A.; Beller, M. (Org. Biomol. Chem., 2010)

(untitled) - Pews-Davtyan, A.; Beller, M. (Chem. Commun., 2011)

(untitled) - Safrygin, A.; Krivosheyeva, E.; Dar’in, D.; Krasavin, M. (Synthesis, 2018)

(untitled) - Safrygin, A.; Dar'in, D.; Lukin, A.; Bakholdina, A.; Sapegin, A.; Krasavin, M. (Tetrahedron Lett., 2019)

PCT Int. Appl. - Samajdar, S.; Abbineni, C.; Sasmal, S.; Hosahalli, S. (Bicyclic heterocyclic derivatives as bromodomain inhibitors, 2018)
Chem. Abstr. 2015, 163, 231586.

US Pat. Appl. - Armani, E.; Capaldi, C.; Sutton, J. M.; Heald, R. A. (Novel compounds, 2016)
Chem. Abstr. 2016, 165, 69015.

(untitled) - Žula, A.; Kikelj, D.; Ilaš, J. (Mini-Rev. Med. Chem., 2013)